Cr doped TiO2 supported on TUD-1 photocatalyst for congo red photodegradation - Yee, Khai Ooi (2014)
A series of new visible light driven photocatalysts of 1 mol% Cr doped Ti02 supported on various amount of TUD-1 have been successfully synthesized via sol gel method. XRD analysis revealed that all the Cr-Ti02/x TUD-l (x = 10,20,30,40 and 50 mol%) photocatalysts were in amorphous form. Both Ti02 and Cr were incorporated in the highly porous siliceous matrix. FTIR analysis indicated the existence of Si-O-Ti bonding in all the materials. UV-Vis D R analysis suggested that alteration of Ti species occurred from tetrahedrally to octahedrally coordinated Ti species when higher TUD-1 amount was used as photocatalyst support. However, the amount of TUD-1 did not affect the wavelength response and the band gap energy of the resulted materials. All the materials were having band gap energy of ~2.9 eV. The photocatalytic performance of the synthesized materials was evaluated through the photodegradation of Congo Red under visible light irradiation at 298 K for 5 h. Results showed that all the Cr-TiO2/TU D -1 materials had higher photocatalytic activity compared to Cr-TiO2, Amongst, Cr-TiO2/30TU D-1 appeared as the most superior photocatalyst that gave the highest percentage of dye degradation.